2020
DOI: 10.1111/add.15250
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in frequency of hookah smoking among youth and adults: findings from waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) study, 2013–15

Abstract: Background and Aims The prevalence of hookah smoking has increased in the United States since at least 2010, especially among youth and young adults. This study assessed self‐reported reasons for hookah smoking cessation and transition to or maintenance of high‐frequency hookah smoking among current hookah smokers. Design Separately analyzed data from the Population Assessment of Tobacco and Health (PATH) study, a longitudinal cohort study. Frequency of and reasons for hookah smoking were ascertained at wave 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…In line with previous literature, 28 , 29 , 30 , 35 , 36 , 37 , 38 several sociodemographics were included at baseline (W3 or W4): age (18–24, 25–44, 45–64, or 65+ years), sex (male or female), sexual orientation (lesbian, gay, bisexual, something else (LGB) or straight), race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, or other races (i.e., all other races, more than one race), annual household income (less than $25,000, $25,000–$49,999, $50,000–$99,999, or $100,000 or more), and educational attainment (less than high school or GED, high school graduate, some college, bachelor’s degree or more).…”
Section: Methodssupporting
confidence: 91%
“…In line with previous literature, 28 , 29 , 30 , 35 , 36 , 37 , 38 several sociodemographics were included at baseline (W3 or W4): age (18–24, 25–44, 45–64, or 65+ years), sex (male or female), sexual orientation (lesbian, gay, bisexual, something else (LGB) or straight), race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, or other races (i.e., all other races, more than one race), annual household income (less than $25,000, $25,000–$49,999, $50,000–$99,999, or $100,000 or more), and educational attainment (less than high school or GED, high school graduate, some college, bachelor’s degree or more).…”
Section: Methodssupporting
confidence: 91%
“…While many studies have examined the transition from susceptibility to ever use across 1 or 2 years of follow-up for e-cigarettes, cigarettes, and hookah, 9,13,14,16,17 as well as research on transitions and trajectories of multiple TP use, 18-26 there is a paucity of research on exploring transition patterns among never users who are susceptible and never users who are non-susceptible, to ever use and progression of TP use, especially with extended follow-up time. This study sought to fill this gap, namely, to identify, visualize, and describe within-product tobacco use longitudinal transition patterns for: e-cigarettes, cigarettes, and hookah by 3 age groups: 12-14-year-olds, 15-17-year-olds, and 18-20-year-olds among never users of each TP in 2014-2015 and follow-up until 2018-2019 using the Population Assessment of Tobacco and Health (PATH) study in the U.S.A. Our analyses describe these longitudinal transition patterns of from never users of each TP who are susceptible and those who are not susceptible to each TP in 2014-2015 by each age group.…”
Section: Introductionmentioning
confidence: 99%
“…Waterpipe smoking (WPS, also known as hookah, shisha, nargileh, and hubble-bubble) has an estimated prevalence of 100 million worldwide, mostly among adolescents of the Middle East [4,5] A Lebanon-based longitudinal study including 228 exclusive WPS adolescent smokers revealed that nicotine dependence among WPS was associated with initiating smoking at a younger age and believing that WP smokers have more friends among other factors [6]. In addition, its affordability and the large number of flavor options transformed this smoking habit into a popular social activity among youngsters in the Middle East [7]. A study involving five Palestinian universities revealed that WPS was 24.4% among students which surpassed the 18% for cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%